Communications [technology 1999 analysis and forecast]. - Riezenman, M.J (IEEE spectrum)
Never before in the field of electronic communication has so much been changed so rapidly by so many. All over the world, engineers are adding new service capabilities and refining old ones. Meanwhile, business entities merge and split in a frantic attempt to stay profitable in an industry whose ramifications and future are becoming increasingly unclear. Part of the confusion, of course, comes from an untried concept in the communications business: local competition. Making the situation even more interesting, the Internet has evolved from a quirky tool into what might well be the future basis for long-distance telephony. On the cellular front, satellite based systems that provide truly worldwide access have become a reality though whether they will be a profitable one remains to be seen. While that drama is playing out, cellular operators and equipment suppliers are hotly debating the nature of the third generation (the second digital generation) of cell phones and services. In local-area networks, Gigabit Ethernet has gone from infancy to early adulthood in about 18 months, while asynchronous transfer mode (ATM) has established itself in wide-area nets, it may yet realize its potential in local-area nets as well